2021
DOI: 10.1186/s12887-021-02597-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of equine-assisted activities on attention and quality of life in children with cerebral palsy in a randomized trial: examining the comorbidity with attention-deficit/hyperactivity disorder

Abstract: Background Attention problems and decreased quality of life are frequently accompanied in Cerebral Palsy (CP), which can negatively affect rehabilitation of physical disability. However, the majority of affected children remain untreated in the aspects of attention or psychosocial factors. Equine-Assisted Activities and Therapies (EAAT) use horse as a therapeutic modality including grooming as well as mounted riding activities in which patients exercise and experience mounted stimulation. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…This study demonstrates quite positive outcomes for children and adolescents with mental ill health who took part in an EAS intervention. Our findings are in line with other EAS studies with participants who had autism spectrum disorders (Xiao et al, 2023 ), attention-deficit/hyperactivity disorder, or cerebral palsy (Ahn et al, 2021 ). Therefore, it could be argued that the findings are transferable to different contexts and children or adolescents with different health problems.…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrates quite positive outcomes for children and adolescents with mental ill health who took part in an EAS intervention. Our findings are in line with other EAS studies with participants who had autism spectrum disorders (Xiao et al, 2023 ), attention-deficit/hyperactivity disorder, or cerebral palsy (Ahn et al, 2021 ). Therefore, it could be argued that the findings are transferable to different contexts and children or adolescents with different health problems.…”
Section: Discussionsupporting
confidence: 92%
“…The included experimental and control groups’ mean age was less than or equal to 16 years. Interventions included cognitive-motor training (6 studies) ( Hoza et al, 2015 ; Pan et al, 2016 ; Meßler et al, 2018 ; Benzing and Schmidt, 2019 ; Kadri et al, 2019 ; Mansson et al, 2019 ), combination exercise (6 studies) ( Kang et al, 2011 ; Choi et al, 2015 ; Ziereis and Jansen, 2015 ; Bustamante et al, 2016 ; Memarmoghaddam et al, 2016 ; Lee et al, 2017 ), traditional aerobic exercise (5 studies) ( Ahmed and Mohamed, 2011 ; Hoza et al, 2015 ; Gelade et al, 2017 ; Meßler et al, 2018 ; Kadri et al, 2019 ), acute aerobic exercise (4 studies) ( Chang et al, 2012 ; Gawrilow et al, 2016 ; Ludyga et al, 2017 ; Benzing et al, 2018 ), aquatic exercise (3 studies) ( Chang et al, 2014 ; Da Silva et al, 2020 ; Sabzi et al, 2021 ), horsemanship (3 studies) ( García-Gómez et al, 2016 ; Oh et al, 2018 ; Ahn et al, 2021 ), perceptual-motor training (3 studies) ( Yazd et al, 2015 ; Hattabi et al, 2019 ; Sani et al, 2022 ), mind-body exercise (2 studies) ( Jensen and Kenny, 2004 ; Milligan et al, 2019 ), as well as sensory integration training (1 study) ( Faramarzi et al, 2016 ). The outcome indicators for ADHD consisted of motor ability, social problems, attention problems, cognitive flexibility, inhibition switching, as well as the working memory.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies ( Jensen and Kenny, 2004 ; Ahmed and Mohamed, 2011 ; Kang et al, 2011 ; Hoza et al, 2015 ; Bustamante et al, 2016 ; García-Gómez et al, 2016 ; Janssen et al, 2016 ; Pan et al, 2016 ; Meßler et al, 2018 ; Oh et al, 2018 ; Kadri et al, 2019 ; Milligan et al, 2019 ; Da Silva et al, 2020 ; Ahn et al, 2021 ) reported on the attention problems of children with ADHD, and a total of ten interventions are involved. As shown in Table 3 , there is no statistical significance for each intervention in the network meta-analysis results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After full-text reading, 111 articles were further excluded, of which 44 did not report the outcomes of interest, 30 had inconsistency in experimental design, 8 had no full-text available, and 29 had no available data. Finally, 10 studies (Jensen and Kenny, 2004;Kang et al, 2011;Hoza et al, 2015;Bustamante et al, 2016;García-Gómez et al, 2016;Pan et al, 2016;Geladé et al, 2017;Oh et al, 2018;Silva et al, 2020;Ahn et al, 2021) were included for quantitative synthesis (Figure 1). The inter-rater reliability between the two reviewers at this stage was classified as good (Cohen's kappa = 0.79).…”
Section: Trial Selectionmentioning
confidence: 99%